SURGICAL TREATMENT OF CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION: MODERN TRENDS AND OWN EXPERIENCE - R. S. Akchurin; K. V. Mershin; E. A. Tabakyan; R. S. Latypov; V. V. Gazizov; D. D. Tsyrenov (Евразийский Кардиологический Журнал, 2016)
Pulmonary endarterectomy (PEA) is the method of choice in treatment of chronic thromboembolic pulmonary hypertension (CTEPH). There are a lot of factors still restricting the widespread use of these operations. Among them are the difficulties of diagnosing and patient selection, the peculiarities of operation and postoperative treatment, the unawareness of cardiological community about surgical outcomes. We discuss the preparation of the patient to PEA, standards of the surgery and postoperative treatment. The results of preoperative diagnostics and PEA-operations at our center are presented. The possible causes of postopreative mortality and adverse outcomes are also discussed.